Investigating the Relationship between Double Reduction Policies, Academic Pressure, and Student Well-being in China's Compulsory Education System - Meng, Qingxin; Mansor, Azlin Norhaini; Omar, Marlissa; Li, Lili; Zheng, Jiao (Journal of Ecohumanism, 2024)
The purpose of this study is to understand the effects of China’s Double Reduction policy on stress and wellbeing of middle school students. This aims at assessing the consequences of the Double Reduction policy in China for middle school learners not only in terms of academic stress. They reveal how academic stress interferes with different aspects of human functioning that include cognitive and physical health and perceived well-being. In addition, it explores the moderating effect of the Double Reduction policy on the association between self-rated health and student academic quality. The main goals of the research include the assessment of the Double Reduction policy and its effects in moderating the level of academic stress among the middle school students in China. Besides it also determines the impact of load decrement on academic performance, in addition to valuing different measures of wellbeing such as mental, physical health and life satisfaction. Additionally, it also explores the moderating effect brought by academic quality in the relationship between the Double Reduction policy and students’ well-being. More specifically, 209 students were hired for the sample and regression analysis was employed in assessing the policy called the Double Reduction policy in which the stress level was found to have been significantly decreased with the well-being of students enhanced as well. The results derived from regression analysis pointed to the great extent of predictive validity. This study also identifies understanding to mean both academic success for students and student care in order to relieve student pressure. The future studies should adopt the longitudinal research designs, subjects of different education levels and employ the objective measures to complement and extend these findings.